Penerapan Metode Fuzzy Sugeno untuk Mengevaluasi Hasil Belajar Siswa - Amir Salim Khairul Rijal (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
Student learning evaluation is a crucial aspect of measuring the level of understanding and achievement of competencies. Traditional assessments are often limited to quantitative scores, such as exams and assignments, which do not consider other aspects like creativity and deep comprehension. This study aims to develop and implement a Fuzzy Sugeno-based evaluation system for the Interactive Media Design course at the Vocational High School (SMK) level. This method integrates various factors, such as assignment and exam scores, using Fuzzy rules to produce a more comprehensive assessment.The research was conducted using MATLAB software for simulating and implementing the Fuzzy Inference System (FIS). The results demonstrated that the method is effective in providing recommendations and assisting teachers in categorizing student scores. Data analysis revealed that the majority of final student scores fall into the Highly Adequate category.The Fuzzy Sugeno method has proven to be flexible in handling uncertainties and offers a fair, transparent, and holistic solution for evaluations. Therefore, this method is recommended as a valuable tool to enhance the quality of student learning assessments in education.